The Global World Order in the Mirror of the International Likhachev Scientific Readings. Book Review of ‘The Growth of a Global Culture and the Clash of Civilizations’ by A.S. Zapesotsky - V. V. Kochetkov (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The International Likhachev Scientific Readings is a unique phenomenon not only for the Russian but for the universal academic and social thought as well. The review examines a fundamental work by A.S.Zapesotsky, a Rector of St. Petersburg University of the Humanities and Social Sciences– one of the initiators of the International Likhachev Scientific Readings. The book contains selected papers of the participants of the Likhachev Readings throughout their history, organized thematically. The reviewer provides a detailed description of all sections of the book, which cover a wide range of issues of contemporary world politics, from globalization, promotion of the dialogue between cultures and civilizations, to the emergence of the postindustrial culture and the new world order. The reviewer emphasizes that the book places a special focus on the role of Russia in the globalized world. Addressing the current trends in the development of the Western, especially European, society, A.S. Zapesotsky highlights a growing civilizational crisis of capitalism and outlines the contours of the new, post-capitalist world order. The book under review also contains proceedings of several round-tables, held during the Likhachev Readings, which addressed the issues of nations and nationalism, conflict of cultures and international terrorism. The reviewer concludes that this book allows for a better understanding of the phenomenon of the Likhachev Readings as a unique moulding of ideas and views of the leading Russian and foreign experts on the key issues of the world politics, globalization and inter-civilizational interaction.